Strategi Pemerintahan Desa dalam Menanggulangi Kecanduan Gadget Melalui Program Ramah Anak - Dalimunthe, Irwan Saleh; Arfandi, Muhammad; Hamidah, Hamidah (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
Islamic education plays an important role in shaping the character of students in accordance with the values ​​of Islamic teachings. One of the main sources in understanding the characteristics of Islamic educators is the hadith of the Prophet Muhammad SAW, which provides guidelines on the nature, ethics, and methods that an educator must have. This study aims to reveal the ideal characteristics of Islamic educators based on the perspective of the hadith of the Prophet Muhammad SAW. Using a qualitative method based on literature studies, this study examines various hadiths related to the characteristics of educators, such as sincerity, patience, compassion, wisdom, and exemplary behavior. The results of the study indicate that an Islamic educator must have high moral integrity, be able to build good relationships with students, and teach knowledge with wisdom and gentleness. These findings contribute to enriching insight into Islamic education and become a guideline for educators in carrying out their duties in accordance with the teachings of the Prophet Muhammad Saw.